Digital signal processing using MATLAB for students and researchers - Leis, John, 1966- (Hoboken, NJ : John Wiley & Sons, 2011)
"This book uses an active learning approach to the topic of digital signal processing (DSP). DSP is a fundamental technology with wide ranging applications as, for example, digital downloads of movies, mobile and broadband communications, digital television, and many other areas. In this book the subject is taught using a "hands-on" experimental approach with MATLAB examples throughout the text to illustrate the mathematical concepts and DSP algorithms developed and explained. Existing books in this area tends to fall into one of two camps - either a highly mathematical treatment with few practical examples of the everyday uses of DSP, or else very verbose and descriptive treatments with little or no mathematical content to back up the topics. The former type of text is excellent as a standard reference, but poor as a learning vehicle. The latter type of text is good for general knowledge, but fails to meet the needs of University students and practicing industry professionals. Students need a learn-by-doing approach, and industry professionals need to come up to speed as rapidly as possible. The book uses MATLAB throughout, inn an established industry and University programming environment. Furthermore, it requires that the reader only have access to the Student/Educational version of MATLAB, not the full commercial version, which is out of reach of most students"--
What is Signal Processing? -- MATLAB for Signal Processing -- Sampled Signals and Digital Processing -- Random Signals -- Representing Signals and Systems -- Temporal and Spatial Signal Processing -- Frequency Analysis of Signals -- Discrete-Time Filters -- Recursive Filters.
Includes bibliographical references and index.
Print version record.
Keywords: MATLAB; MATLAB; MATLAB; Signal processing -- Digital techniques; Signal processing -- Mathematics -- Data processing; Signal processing -- Digital techniques; Signal processing -- Mathematics -- Data processing; COMPUTERS -- Information Theory; TECHNOLOGY & ENGINEERING -- Signals & Signal Processing; Signal processing / Digital techniques; Signal processing / Mathematics / Data processing; Electronic books